Nano-bioceramic synthesis from tropical sea snail shells (Tiger Cowrie - Cypraea Tigris) with simple chemical treatment - (:unkn) unknown (My University, 2015)
In this study several bioceramic materials (i.e. hydroxyapatite, whitlockite) were prepared by using chemical synthesis method from sea snail shells (Tiger Cowrie - Cypraea Tigris), originated from Pacific Ocean. Marine shells usually present aragonite-calcite structures and generally, complicated and pressurized equipment is necessary to convert these structures into bioceramics. Instead of using complicated systems, a basic ultrasonic equipment and simple chemical synthesis method was used in the process. DTA analysis was performed to calculate the required amount of H3PO4 solution in order to set the appropriate stoichiometric ratio of Ca/P equal to 1.667 for HA bioceramic or to 1.5 for β-TCP bioceramic in the titration. The prepared batches were sintered at 800°C and 400 °C for hydroxyapatite (HA) and β-tri calcium phosphate (β-TCP) forms respectively. X-ray diffraction analysis, scanning electron microscopy (SEM) and infrared observations (FTIR) were implemented for both TCP and HA bioceramics. By applying the chemical synthesis with basic ultrasonic equipment, this study proposes a simple way of production for nano-HA/TCP powders from a natural marine sources.
Keywords: Fizik; Astronomi ve Astrofizik; Temel Bilimler; Physics; Astronomy and Astrophysics; Natural Sciences; Temel Bilimler (SCI); Uzay bilimi; ASTRONOMİ VE ASTROFİZİK; Natural Sciences (SCI); SPACE SCIENCE; ASTRONOMY & ASTROPHYSICS; Genel Fizik ve Astronomi; Fizik Bilimleri; General Physics and Astronomy; Physical Sciences